2013
DOI: 10.1016/s1470-2045(13)70096-2
|View full text |Cite|
|
Sign up to set email alerts
|

Epirubicin, oxaliplatin, and capecitabine with or without panitumumab for patients with previously untreated advanced oesophagogastric cancer (REAL3): a randomised, open-label phase 3 trial

Abstract: SummaryBackgroundEGFR overexpression occurs in 27–55% of oesophagogastric adenocarcinomas, and correlates with poor prognosis. We aimed to assess addition of the anti-EGFR antibody panitumumab to epirubicin, oxaliplatin, and capecitabine (EOC) in patients with advanced oesophagogastric adenocarcinoma.MethodsIn this randomised, open-label phase 3 trial (REAL3), we enrolled patients with untreated, metastatic, or locally advanced oesophagogastric adenocarcinoma at 63 centres (tertiary referral centres, teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
387
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(418 citation statements)
references
References 25 publications
9
387
1
6
Order By: Relevance
“…In contrast to the success obtained with trastuzumab in advanced GC, monoclonal antibodies that target HER1 (epidermal growth factor receptor, EGFR) have failed to improve outcome in biologically unselected GC patients [36,59]. It remains to be elucidated from tumor tissue analyses if a small proportion of GC patients may benefit from anti-EGFR targeted therapy, e.g., in the case of EGFR gene amplification [60].…”
Section: Biologically Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the success obtained with trastuzumab in advanced GC, monoclonal antibodies that target HER1 (epidermal growth factor receptor, EGFR) have failed to improve outcome in biologically unselected GC patients [36,59]. It remains to be elucidated from tumor tissue analyses if a small proportion of GC patients may benefit from anti-EGFR targeted therapy, e.g., in the case of EGFR gene amplification [60].…”
Section: Biologically Targeted Therapymentioning
confidence: 99%
“…3). Ramucirumab has also been shown to prolong the survival time with a very reasonable side-effect profile [59], but this anti-angiogenic antibody is not yet on the market.…”
Section: Post-progression Treatmentmentioning
confidence: 99%
“…The ToGA (Trastuzumab for Gastric Cancer) trial has shown that trastuzumab improves the survival of patients with HER2 protein-overexpressing and/or HER2 geneamplifying advanced gastric cancer [5]. Although the addition of cetuximab or panitumumab to chemotherapy in non-molecularly selected gastric cancer patients did not improve survival [6,7], a phase 2 study has shown a possible improvement in the survival of the patient subset with high EGFR expression who were treated with nimotuzumab, a humanized monoclonal antibody to EGFR [8]. At present, a phase 3 nimotuzumab trial (ENRICH study) in patients with EGFR-overexpressing advanced gastric and gastroesophageal junction cancer is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…EGFR overexpression and gene amplification serve as effective biomarkers for predicting the clinical benefit of anti-EGFR monoclonal antibodies for treating colorectal [17] and lung cancer [18]. The recent REAL3 (panitumumab) [19] and EXPAND (cetuximab) [20] randomized controlled phase III trials failed to demonstrate the efficacy of the anti-EGFR monoclonal antibodies for treating gastric cancer, presumably because precise patient inclusion criteria were not set for the trials. Several studies suggest that EGFR overexpression or gene amplification may serve as a potential biomarker for the efficacies of anti-EGFR therapies in gastric cancer [9,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%